The effect of price strategy on customers perception for Boer Goats in Koperasi Permodalan Melayu Negeri Johor (KPMNJ) / Mohd Izri Yatiman - Yatiman, Mohd Izri (Faculty of Business and Management, 2011)
The purpose of this research is to know the effect of price strategy for Boer Goats in Koperasi Permodalan Melayu Negeri Johor (KPMNJ). KPMNJ have subsidiaries which are KPMNJ Gold Sdn Bhd, Executive Travel & Tours (M) Sdn Bhd, Kayu Utama Sendirian Berhad, KPMJ Holdings Sdn Bhd, KPMJ Khidmat Sdn Bhd, and KPMJ Properties Sdn Bhd. The selling of Boer Goats is under Kayu Utama Sdn Bhd. There are lack of awareness of customers regarding the selling of Boer Goats by KPMNJ. It is due to the price strategy to make the selling.The main objective of this research is to identify the most effect of price strategy to influence the customer perception. The research is conducted by using non probability sampling and the sampling method is convenience sampling. 50 of respondents will be asking by using questionnaire in order to gain information and feedback to the company. The questionnaire consists of question about the perception of customer towards the price of KPMNJ Boer Goats. The data that I will obtain are the analysis via the usage of manual coding and is then interpreted by using different types of illustrations. The types of illustrations used are tables, bar charts and graphs. There are three limitations that I will need to face upon completion of this research later in the future. Those are time limitations, respondent commitment and also human error. Thus, the conclusion is that the research proposal will benefit many people and especially KPMNJ.